A Study on The Current Practices of Safety and Health by Contractor in The Construction Industry at Sarawak - anak Jarup, Jeurane Alto; Tami, Hannifah (Journal of Structural Monitoring and Built Environment, 2025)
The Occupational Safety and Health (Amendment) Act 2022 expanded the scope of Malaysia's Occupational Safety and Health Act 1994 to include all workplaces, emphasizing stricter safety regulations and penalties. Despite this, the construction sector, particularly in rapidly urbanizing Sarawak, remains high-risk, significantly contributing to occupational fatalities. This study aims to assess current safety and health practices among contractors in Sarawak's construction industry and propose improvements. Focusing on Sri Aman, Sibu, and Bintulu, data were collected through questionnaires and observations, analyzing management, social, and risk control aspects. Findings reveal that while safety practices are implemented, further improvements are essential to enhance worker well-being and safety stewardship in the region.